Child feeding style is associated with food intake and linear growth in rural Ethiopia - Abebe, Zeweter; Haki, Gulelat Desse; Baye, Kaleab (Appetite, 2017)
Little is known about mother-child feeding interactions and how this is associated with food intake and linear growth. To characterize mother-child feeding styles and investigate their associations with accepted mouthful and linear growth in west Gojam, rural Ethiopia. Two, in-home, meal observations of children aged 12–23 months (n = 100) were video-taped. The number of mouthful accepted was counted and the caregiver/child feeding styles were coded into positive/negative categories of self-feeding, responsive-feeding, active-feeding, social-behavior and distraction. Data on socio-demographic characteristics, child feeding practices, perception about child's overall appetite, and strategies adopted to overcome food refusal were collected through questionnaire-based interviews. Child and mothers' anthropometric measurements were also taken. Stunting was highly prevalent (48%) and the number of mouthful accepted was very low. Offering breastmilk and threatening to harm were the main strategies adopted to overcome food refusal. Although all forms of feeding style were present, active positive feeding style was dominant (90%) and was positively associated with mouthful accepted. Talking with non-feeding partner (64%), and domestic animals (24%) surrounding the feeding place were common distractions of feeding. Feeding was mostly terminated by caregivers (75%), often prematurely. Overall, caregivers of stunted children had poorer complementary- and breast-feeding practices and were less responsive to child's hunger and satiation cues (P < 0.05). Positive responsive feeding behaviors were associated with child's number of mouthful accepted (r = 0.27; P = 0.007) and stunting (r = 0.4; P < 0.001). Low complementary food intake in this setting is associated with caregivers’ feeding style and stunting. Nutrition interventions that reinforce messages of optimal infant and young child feeding and integrate the promotion of responsive feeding behaviors are needed.